Preoperative supplementation of calcitriol and calcium relieves symptom and extent of hypocalcemia in patients undergoing total thyroidectomy and bilateral central compartment neck dissection: A prospective, randomized, open-label, parallel-controlled clinical study - Li, Dapeng; Tian, Mengran; Zhang, Yan; Yu, Yang; Cheng, Wenyuan; Li, Yigong; Wang, Junyi; Wei, Songfeng; Wang, Xin; Yang, Xiaoyong; Zhao, Jingzhu; Yun, Xinwei; et al. (Frontiers in Oncology, 2022)
Background Hypocalcemia is the most common complication that challenges surgeons performing total thyroidectomy. Conventional postoperative calcium and calcitriol supplement has been reportedly effective; however, a time lag has been reported before taking effect. Therefore, the role of preoperative strategy is yet to be determined. Study design In this prospective, randomized, open-label, parallel-controlled phase II clinical study (registration number: ChiCTR2200059815), a short-term preoperative administration of calcitriol and calcium was proposed in 210 patients undergoing total thyroidectomy and bilateral central compartment neck dissection. Patients were recruited and randomized (1:1:1) into three groups: (A) combined (preoperative calcitriol and calcium), (B) calcium only (preoperative calcium only), and (C) control (no preoperative intervention). Finally, a total of 172 patients were qualified for final analysis. Results Our data showed that 16 of 63 patients (25.4%) in the combined group had symptomatic hypocalcemia, whereas more patients from the control group (25 of 57 patients, 43.9%, P = 0.033) had symptomatic hypocalcemia. Further, the postoperative calcium level in the combined group is higher than in the control group (2.15 ± 0.15 vs. 2.09 ± 0.15 mmol/L, P = 0.031). Moreover, patients from the combined group showed lower calcium rates of <2.00 mmol/L (12.7% vs. 28.1%, P = 0.036). Remarkably, compared with the control group, patients with transient hypoparathyroidism in the combined group showed fewer rates for both symptomatic and biochemical hypocalcemia (28.6% vs. 61.1% for symptomatic hypocalcemia; 47.6% vs. 75% for biochemical hypocalcemia). Patients without transient hypoparathyroidism in all three groups showed no significant difference in rates for either symptomatic or biochemical hypocalcemia, indicating that this preoperative strategy is only effective for patients with transient hypoparathyroidism. We did not observe such beneficial effects in patients from the calcium group. Conclusions Preoperative administration of calcitriol and calcium could reduce symptomatic and biochemical hypocalcemia, especially for those with transient hypoparathyroidism. Moreover, this maneuver could be recommended as a clinical routine in patients undergoing total thyroidectomy and bilateral central compartment neck dissection. Clinical Trial Registration http://www.chictr.org.cn/edit.aspx?pid=164316&htm=4, identifier ChiCTR2200059815.